IDEOLOGI GURU BAHASA INDONESIA LIBERAL - Agus Purnomo Ahmad Putikadyanto; Abd. Syukur Ibrahim; Nurchasanah Nurchasanah (Graduate School of Universitas Negeri Malang, 2017)
This research aims at investigating liberal life perspective of Indonesian language teacher at SMK Kartika IV-1 Malang in regard with general education objective, school aims, general characteristics, children as learners, management and administration, curriculum characteristics, learning subject materials, learning method, learning evaluation and classroom management. This research employed qualitative design using case study approach. The subject of this research were liberal Indonesian language teachers at SMK Kartika IV-1 Malang. The data of this research were obtained through in-depth interview and observation. The obtained data then were analyzed using Education Ideology Mapping by O’Neil (2008). The results of this study indicated that life perspective of liberal Indonesian language teachers at SMK Kartika IV-1 regarding general education objective, school aims, general characteristics, children as learners, management and administration, curriculum characteristics, learning subject materials, learning method, learning evaluation and classroom management is diversed. However, life perspective of liberal Indonesian language teachers at SMK Kartika IV-1 is not constantly similar with Education Ideology Mapping by O’Neil.Penelitian ini bertujuan untuk mendeskripsikan pandangan hidup guru bahasa Indonesia SMK Kartika IV-1 Malang yang berideologi liberal tentang tujuan pendidikan secara umum, tujuan sekolah, ciri-ciri umum, anak sebagai pelajar, administrasi dan pengendalian, sifat-sifat kurikulum, implementasi mata pelajaran, metode pengajaran dan penilaian hasil belajar, dan kendali di ruang kelas. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian ini adalah guru bahasa Indonesia liberal SMK Kartika IV-1 Malang. Teknik pengumpulan data dalam penelitian ini menggunakan teknik wawancara yang mendalam dan observasi. Analisis data menggunakan rambu-rambu ideologi pendidikan O’Neil (2008). Hasil penelitian ini adalah pandangan hidup guru bahasa Indonesia liberal SMK Kartika IV-1 Malang tentang tujuan pendidikan secara umum, tujuan sekolah, ciri-ciri umum, anak sebagai pelajar, administrasi dan pengendalian, sifat-sifat kurikulum, implementasi mata pelajaran, metode pengajaran dan penilaian hasil belajar, dan kendali di ruang kelas beragam. Akan tetapi, pandangan hidup guru bahasa Indonesia liberal SMK Kartika IV-1 Malang tidak selalu sama dengan teori rambu-rambu ideologi pendidikan liberal O’Neil.